2009
DOI: 10.1007/s00468-009-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of coffee leaf photosynthesis by stomatal conductance and light availability under different shade levels

Abstract: In agroforestry systems, the effect of shade trees on coffee net photosynthesis (A n ) has been the object of debates among coffee scientists. In this study, we undertook over 600 coffee A n ''spot'' measurements under four different artificial shade levels (100, 72, 45 and 19% of full solar irradiance) and analyzed limitations to A n by low light availability (photon flux density, PFD) and stomatal conductance (g s ). These gas exchange measurements were carried out during two consecutive coffee growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 32 publications
4
35
1
4
Order By: Relevance
“…These observations of higher g s and higher A net have also been reported by other findings as in citrus plant (Medina et al, 2002). This has been explained by Franck and Vaast (2009) that this condition was linked to lower diffusional limitation. Lower E L value in T4 caused by the higher temperature received by the plants thus might lead to loss of water.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These observations of higher g s and higher A net have also been reported by other findings as in citrus plant (Medina et al, 2002). This has been explained by Franck and Vaast (2009) that this condition was linked to lower diffusional limitation. Lower E L value in T4 caused by the higher temperature received by the plants thus might lead to loss of water.…”
Section: Discussionsupporting
confidence: 88%
“…This result as evidence that lower value of g s might point towards to reduction on the A net value and this was parallel as g s principally affected the diffusional limitation (Larcher, 2003) shows leading in the stomatal limitation. Consequently, this result may due to this condition leads almost to stomatal closure in which stomatal closure generally will reduced the diffusion of ambient CO 2 into mesophyll (Elsheery and Cao, 2008.;Franck and Vaast, 2009), thus resulted in the A net reduction (Cornic, 2002). Higher value of g s in 2 and T3 associated to the high value of A net if compared to the exposed plants of T4.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the average intercept of 47% observed in this work is within the range proposed by those authors. Studies on arabica coffee grown under agroforestry systems have shown limitations for both stomatal conductance and light availability for coffee photosynthesis under shade levels above 45% (Franck and Vaast, 2009). Carelli et al (1999) observed significant reductions in photosynthesis and stomatal conductance with light interception of 80%; however, they found no differences in these variables with a light interception of 50%.…”
Section: Microclimate Characterizationmentioning
confidence: 99%
“…The higher humidity at the shaded area was in accordance with Barradas and Fanjul (1986), who explained it by higher output of water vapour produced by a much higher transpiration rate of canopy trees pumping water from lower soil layers. Additionally, shade of up to 55% is beneficial for coffee leaf photosynthesis as it maintains greater coffee net photosynthesis relative to plants in full sun via a significant attenuation of stomatal stress (Franck and Vaast, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, C. arabica is shade-adapted, with leaves that can maintain a high photosynthetic performance under low light availability (Franck and Vaast, 2009), making it well-suited to heavily shaded systems. Agroforestry provides additional benefits not yielded by coffee plantations grown in full sun, including serving as a refuge for forest biota (Moguel and Toledo, 1999), reducing pressure for further forest conversion to agriculture (Noponen et al, 2013), serving as a source of fuel-wood and construction material (Rice, 2008), stabilizing microclimatic conditions (Lin, 2007;Siles et al, 2010a), and protecting the soil (Siebert, 2002).…”
Section: Introductionmentioning
confidence: 99%